Basic Principles of Leading Methods in Translating Folklore Works - Fayzulloev O.M.; Muxamadova A.O. (Indonesian Journal of Innovation Studies, 2022)
The article discusses basic principles of leading methods in translating folklore works and takes into consideration various methods of translating of literary texts.